2004
DOI: 10.1093/jn/134.4.799
|View full text |Cite
|
Sign up to set email alerts
|

Mice Heterozygous for Atp10c, a Putative Amphipath, Represent a Novel Model of Obesity and Type 2 Diabetes

Abstract: Atp10c is a novel type IV P-type ATPase and is a putative phospholipid transporter. The purpose of this study was to assess the overall effect of the heterozygous deletion of Atp10c on obesity-related phenotypes and metabolic abnormalities in mice fed a high-fat diet. Heterozygous mice with maternal inheritance of Atp10c were compared with heterozygous mice with paternal inheritance of Atp10c and wild-type controls. Body weight, adiposity index, and plasma insulin, leptin and triglyceride concentrations were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 24 publications
4
75
1
Order By: Relevance
“…Angelman syndrome, which is characterized by neurologic abnormalities, including mental retardation, ataxia, and epilepsy (70), and behavioral disorders, such as autism (71), have been linked to ATP10C. A mouse homolog of ATP10C (pfatp) has been associated with obesity and may be a new model for Type 2 diabetes (72). How the putative role of the P 4 -ATPases in membrane structure and function influences these diseases remains to be determined.…”
Section: P 4 -Atpasesmentioning
confidence: 99%
“…Angelman syndrome, which is characterized by neurologic abnormalities, including mental retardation, ataxia, and epilepsy (70), and behavioral disorders, such as autism (71), have been linked to ATP10C. A mouse homolog of ATP10C (pfatp) has been associated with obesity and may be a new model for Type 2 diabetes (72). How the putative role of the P 4 -ATPases in membrane structure and function influences these diseases remains to be determined.…”
Section: P 4 -Atpasesmentioning
confidence: 99%
“…Mammalian homologues of Drs2p include the chromaffin granule ATPase II (now called ATP8A1) (Tang et al, 1996), which is likely responsible for a PS translocase activity observed with these exocytic vesicles (Zachowski et al, 1989), and FIC1 (ATP8B1), for which mutations in humans cause an impairment of bile flow through the liver (cholestasis) (Bull et al, 1998;Klomp et al, 2004). In addition, deletions removing the mouse Atp10c gene cause diet-induced obesity and type 2 diabetes phenotypes (Dhar et al, 2004). P4-ATPases are also agriculturally important, because they are required for pathogenesis of the rice blast fungus Magneporthe griseus (Balhadere and Talbot, 2001;Gilbert et al, 2006) and growth of plants at cold temperatures (Gomes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are 14 mammalian P4-ATPases that are associated with intellectual disability (24), neurodegeneration (25), liver disease (26,27), hearing loss (28), diabetes (29), immune deficiency (30,31), anemia (32), and reduced male fertility (33). Budding yeast express the following five members of this subgroup: Dnf1, Dnf2, Dnf3, Drs2, and Neo1.…”
mentioning
confidence: 99%